Valei-me, São Sebastião: a epidemia de cólera morbo na vila de Maranguape (1862-1863) - Maciel, Dhenis Silva (2011)
In this study we sought to understand the epidemic of cholera morbus in the village of Maranguape in 1862 and how this was understood by the individuals that comprised the medical and religious knowledge and the political uses that the epidemic has assumed from the look of liberal parties and conservative. We focus our attention on the actions of doctors who took part in the commission of public relief, the two priests who worked in the village during the illness and the action of public administrators. We aim to understand the disease and its meaning from a broader reading than was the village of Maranguape in 1862, the medical theories that guided and the answers given by religion. To bring out such a venture, we use varied character documents such as reports of the provincial president, letters sent by the commissioned doctors, letters of the priests and members of the chamber of the village, provincial laws, newspapers and chronicles.